Sanqi Oral Solution Mitigates Proteinuria in Rat Passive Heymann Nephritis and Blocks Podocyte Apoptosis via Nrf2/HO-1 Pathway - Wang, Xiaowan; Liu, Jinchu; Tian, Ruimin; Zheng, Bidan; Li, Chuang; Huang, Lihua; Lu, Zhisheng; Zhang, Jing; Mao, Wei; Liu, Bo; Bao, Kun; Xu, Peng (Frontiers in Pharmacology, 2021)
Idiopathic membranous nephropathy (IMN) is the most common pathological type in adult nephrotic syndrome where podocyte apoptosis was found to mediate the development of proteinuria. Sanqi oral solution (SQ), an effective Chinese herbal preparation clinically used in treatment of IMN for decades, plays important role in reducing proteinuria, but the underlying mechanisms have not been fully elucidated yet. The current study tested the hypothesis that SQ directly lessens proteinuria in IMN by reducing podocyte apoptosis. To investigate the effects of SQ, we established the experimental passive Heymann nephritis (PHN) rat model induced by anti-Fx1A antiserum in vivo and a doxorubicin hydrochloride-injured apoptotic podocyte model in vitro. SQ intervention dramatically reduced the level of proteinuria, together with the rat anti-rabbit IgG antibodies, complement C3 and C5b-9 deposition in glomerulus of PHN rats, accompanied by an elevation of serum albumin. Protein expression of Synaptopodin, marker of podocyte injury, restored after SQ administration, whereas the electron microscopic analysis indicated that fusion of foot processes and the pachynsis of glomerular basement membrane was markedly diminished. Further studies showed that SQ treatment could significantly inhibit podocyte apoptosis in PHN rats and ADR-injured podocytes. And protein levels of Cleaved caspase-3 or the ratio of Bax/Bcl-2 were significantly decreased with SQ treatment in vivo or in vitro. Moreover, we found that nuclear factor erythroid-2-related factor-2/heme oxygenase-1 (Nrf2/HO-1) pathway mediated the anti-apoptosis effective of SQ in podocyte. Thus, SQ mitigates podocyte apoptosis and proteinuria in PHN rats via Nrf2/HO-1 pathway.